(untitled) (Contemporary Education and Teaching Research, 2024)
Vocational education plays the role of a bridge connecting education and industry in the development of Guangdong, Hong Kong and Macao Greater Bay Area, and directly serves the needs of major industries in the region by cultivating high-quality skilled personnel. With the rapid development of science and technology and industries, vocational education not only needs to continuously update its curriculum content and teaching methods, but also needs to keep abreast of the times by adopting advanced teaching technologies and tools to keep pace with the development of the industries. This requires the vocational education quality assurance system to be constantly innovated and improved in terms of standardization, internationalization, informatization and intelligence. This paper discusses the construction of the quality assurance system of vocational education under the leadership of the qualifications framework, focusing on the analysis of the standardization and internationalization strategies, informatization and intelligence strategies, teacher team building and professional development strategies, as well as the strategies of school-enterprise cooperation and industry-teaching integration, with the aim of providing theoretical support and practical references for improving the quality of vocational education in the Greater Bay Area.